2013
DOI: 10.1371/journal.pone.0072817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Administration of L-Glutamine and Cycloart-23-ene-3β, 25-diol (B2) with Sitagliptin in GLP-1 (7–36) Amide Secretion, Biochemical and Oxidative Stress in Streptozotocin - Nicotinamide Induced Diabetic Sprague Dawley Rats

Abstract: Previously we have reported that, cycloart-23-ene-3β, 25-diol (called as B2) and L-glutamine stimulated glucagon like peptide-1 (GLP-1) (7–36) amide secretion diabetic rats. The objective of present investigation was to investigate the concomitant administration of cycloart-23-ene-3β, 25-diol+sitagliptin and L-glutamine+sitagliptin in streptozotocin - nicotinamide induced diabetic Sprague Dawley. Type 2 diabetes was induced in overnight fasted male Sprague Dawley rats pre-treated with nicotinamide (100 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Diabetic fed with a common semi purified diet, 3. Identical diet with glutamine 25% of total amino acid nitrogen 8 weeks Significant increase GSH Significant decrease CRP, IL-6, IL-23, MCP-1 No significant change Fasting blood Glucose, TGF-β, TNF-α, IL-17A Badole et al, India, 2013 [ 18 ] Rats divided into six groups: 1. Nondiabetic, 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic fed with a common semi purified diet, 3. Identical diet with glutamine 25% of total amino acid nitrogen 8 weeks Significant increase GSH Significant decrease CRP, IL-6, IL-23, MCP-1 No significant change Fasting blood Glucose, TGF-β, TNF-α, IL-17A Badole et al, India, 2013 [ 18 ] Rats divided into six groups: 1. Nondiabetic, 2.…”
Section: Resultsmentioning
confidence: 99%
“…Glutamine 500 mg/kg 6. Glutamine 1000 mg/kg 250–500-1000 mg/kg 8 weeks Significant decrease MDA, fasting blood glucose, LDL,TC, TG Significant increase Plasma and pancreatic insulin, increased GLP-1, amide secretion, GSH, SOD, GPx (only the highest dose), HDL Bdaole et al, India, 2013 [ 18 ] Rats divided into four groups: 1. Non-diabetic, 2.…”
Section: Resultsmentioning
confidence: 99%
“…The neuroprotection caused by L-glutamine in the diabetic group (DG) in this study has been reported in the literature for vipergic [ 12 , 53 ] and general [ 64 ] populations. Supplementation with L-glutamine has proven effective in minimize oxidative stress [ 22 , 28 , 65 , 66 ], increasing its availability to tissues under stress [ 67 ]. The GDP also has antioxidant potential [ 65 ], but its supplementation was not able to protect the submucous neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The essential roles of GLP-1 and GIP in maintaining blood glucose homeostasis have been widely recognized. GLP-1 is an incretin secreted from the intestinal L cells, which regulates blood glucose homeostasis via stimulation of insulin secretion, attenuation of gastric emptying and promotion of satiety 17 38 39 . Many drugs and Chinese herbal medicines improve diabetes by regulating GLP-1 40 .…”
Section: Discussionmentioning
confidence: 99%
“…As an anti-hyperglycemic hormone it acts by stimulating glucose-dependent insulin secretion 13 14 15 . In addition, GLP-1 inhibits gastric secretion and regulates glucose homeostasis in the gastrointestinal tract after meals and is required for normal glucose tolerance 16 17 . Glucose-dependent insulinotropic polypeptide (GIP) is a 42-amino acid peptide localized to the distal intestine, where exists a population of K-/L cells that produce both GIP and GLP-1.…”
mentioning
confidence: 99%